2023
DOI: 10.1177/00219983231168946
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organically-modified montmorillonite and alkalinization on physical, mechanical, chemical, morphological, and thermal properties of wheat straw/recycled polypropylene nanocomposites

Abstract: Valorization of wheat straw fiber/recycled polypropylene nanocomposites was investigated through studying the individual and combined effects of organically modified montmorillonite (OMMT) and alkali treatments on the given composites. FTIR spectra indicated the reduction of wheat straw fibers' hydroxyl groups due to hemicellulose removal resulting from alkali treatment. There were also trace diminutions in C-O peak intensities due to the degradation of little amounts of lignin. X-ray analysis revealed the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 94 publications
0
1
0
Order By: Relevance
“…They are applicable in food packaging, biomedical devices, and automotive industries. [23][24][25][26][27][28][29][30][31][32][33] Hossen et al 34 developed a hybrid composite using polyethene (PE) as the matrix with the addition of dispersed natural jute fibers and nanoclay. In this study, the authors reported that the incorporation of nanoclays improved both the physical and mechanical properties of the hybrid composite.…”
Section: Introductionmentioning
confidence: 99%
“…They are applicable in food packaging, biomedical devices, and automotive industries. [23][24][25][26][27][28][29][30][31][32][33] Hossen et al 34 developed a hybrid composite using polyethene (PE) as the matrix with the addition of dispersed natural jute fibers and nanoclay. In this study, the authors reported that the incorporation of nanoclays improved both the physical and mechanical properties of the hybrid composite.…”
Section: Introductionmentioning
confidence: 99%